Forecast modelling of vegetable oil spill events at Paranaguá Port, Brazil - Schmidt, Luiz Gustavo (2023)
The Port of Paranaguá serves as Brazil's primary outlet for soy oil exports, accounting for nearly 70% of all shipments in 2021. While less common than mineral oil spills, vegetable oil spills can have similarly devastating environmental effects. This risk underscores the need for effective planning and management of activities involving vegetable oil handling in the region. To address this need, this study developed results based on a forecasting setup focused on describing the behaviour of soy oil spills in the estuarine complex of Paranaguá. The system uses the open TELEMAC-MASCARET three-dimensional numerical modelling system to solve oil movement equations, coupling the hydrodynamic module (Telemac-3d) with the oil module (ECOS). The system is automated through computational routines written in Python and the bash command language, enabling users to initiate simulations and generate dispersion maps to track soybean oil in hypothetical spill scenarios. The processing results were satisfactory, demonstrating the potential for this tool to contribute to minimising the impacts of soybean oil spills in the Bay of Paranaguá. This system can support better decision-making in response efforts, reduce environmental damage, and enhance the protection of local ecosystems.